Labour Market Flexibility and Employment Protection Regulation in the Baltic States - Jaan Masso; Raul Eamets (Institute for the Study of Labor (IZA), 2004)
There is increasing pressure for the flexibility of labour markets both in current EU member states and candidate countries. The paper aims to estimate the strictness of employment protection regulation, one of the most relevant aspects of labour market flexibility, and the degree of its actual enforcement, for the Baltic States. For the studies on CEE labour markets the novelty in our approach is that we use information from the applicable legislation as well as on the coverage of labour legislation and the practice of law enforcement. The analysis shows that, though overall EPL strictness is close to the average of EU countries, individual and collective dismissals are relatively heavily and temporary forms of employment relatively weakly regulated. Still, the effective flexibility is increased by larger share of less protected workers and problems with law enforcement, which may be the reason why employers? estimates on the flexibility differ somewhat from the flexibility of formal legislation. The employment protection legislation seems not to have influenced the level of unemployment in the sample of CEE countries. However, it is possible that labour markets of Baltic States will become more rigid if the law enforcement improves, with possible adverse effects on labour market performance.
Keywords: J8; J32; K31; J23; 330; employment protection legislation; labour market flexibility; Baltic States; Arbeitsmarktflexibilisierung; Kündigungsschutz; Arbeitsrecht; Nordosteuropa